Pediatric Multiple Sclerosis Severity Score in a large US cohort. (29th September 2020) - Santoro, Jonathan D.; Waltz, Michael; Aaen, Greg; Belman, Anita; Benson, Leslie; Gorman, Mark; Goyal, Manu S.; Graves, Jennifer S.; Harris, Yolanda; Krupp, Lauren; Lotze, Timothy; Mar, Soe; et al.
Abstract : Objective: To characterize disease severity and distribution of disability in pediatric-onset multiple sclerosis (POMS) and to develop an optimized modeling scale for measuring disability, we performed a multicenter retrospective analysis of disability scores in 873 persons with POMS over time and compared this to previously published data in adults with multiple sclerosis (MS). Methods: This was a retrospective analysis of prospectively collected data collected from 12 centers of the US Network of Pediatric MS Centers. Patients were stratified by the number of years from first symptoms of MS to Expanded Disability Status Scale (EDSS) assessment and an MS severity score (Pediatric Multiple Sclerosis Severity Score [Ped-MSSS]) was calculated per criteria developed by Roxburgh et al. in 2005. Results: In total, 873 patients were evaluated. In our cohort, 52%, 19.4%, and 1.5% of all patients at any time point reached an EDSS of 2.0, 3.0, and 6.0. Comparison of our Ped-MSSS scores and previously published adult Multiple Sclerosis Severity Scores (MSSS) showed slower progression of Ped-MSSS with increasing gaps between higher EDSS score and years after diagnosis. Decile scores in our POMS cohort for EDSS of 2.0, 3.0, and 6.0 were 8.00/9.46/9.94, 7.86/9.39/9.91, and 7.32/9.01/9.86 at 2, 5, and 10 years, respectively. Notable predictors of disease progression in both EDSS and Ped-MSSS models were ever having a motor relapse and EDSS at year 1. Symbol Digit Modalities Test (SDMT) scores were inversely correlated with duration of disease activity and cerebral functional score. Conclusions: Persons with POMS exhibit lower EDSS scores compared to persons with adult-onset MS. Use of a Ped-MSSS model may provide an alternative to EDSS scoring in clinical assessment of disease severity and disability accrual.